Proposing a new format for dispensing powdered beverages in sachets into consumable liquid - Sanz Laurel, Maria Dominique; Tan-Sy, Grace (Quezon City College of Fine Arts, University of the Philippines Diliman, 2006)
Sachets have been used as packaging for quite a few decades. At first made by hand, and now, sachets are made by machines. For as long as the researcher can remember, sachets have always had the same structure or format; with the "tear here" notch, or serrations at the top and bottom of each sachet. There is one thing that interested the researcher about sachets and dispensing powdered juice into consumable liquid, whether it be cups or mineral water bottles. It was that there has always been handling difficulties and hassles encountered when dealing with sachets. With this, the researcher will conduct a study regarding these handling difficulties and attempt to attain a solution.
Thesis (Bachelor of Fine Arts in Visual Communication) - -University of the Philippines Diliman
Bibliography : leaf 37.
Keywords: Beverages -- Design. -- Packaging